EFEKTIVITAS PENGAWASAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENGGUNAAN ALOKASI DANA DESA DI DESA BETELEME KABUPATEN MOROWALI SULAWESI TENGAH - TANSALA, FERDI (Sam Ratulangi University, 2014)
Government of countryside is activity of Governance executed by government of body and countryside parley of countryside. Body parley of countryside which then referred by BPD is parley body which consist of the prominent society exist in functioning countryside mores directions, making regulation of countryside, accomodating and channelling society aspiration and also conduct observation to management of government of countryside. Function of BPD as supervisor (controling) to countryside fund allocation in countryside Beteleme uncommitt maximally. Accurate writer about Effectiveness Observation Of Body Parley of Countryside (BPD) in Usage Of Allocation Fund Countryside Beteleme (Case Study in Countryside Beteleme Sub-Province of Morowali Middle Sulawesi). Writer take informan by purposive sampling, that is technique withdrawal of sampel by intending or showing direct to one who assumed can give information. Technique data collecting that is interview, perception (observasi) and study bibliography. Â Â Keyword : Effectiveness, Observation, Allocate